Issues in Australian foreign policy : July to December 2010 - David Hundt (2011)
Two unforseen developments impeded the Labor government’s capacity to pursue its foreign policy objectives in the period under review. Firstly, Labor’s precarious standing in the parliament tilted the government’s policy agenda in favour of issues that the Greens prioritised. Gillard addressed some of these issues, for instance by holding the parliamentary debate on Afghanistan and by pursuing Japan over whaling in the Southern Ocean, but not to the degree that the Greens demanded. Immigration was emblematic of the government’s travails. The Greens advocated an increase in the refugee intake, but the Coalition favoured the resumption of offshore processing. Just when Labor’s proposed Timorese solution was becoming a realistic possibility, the High Court’s decision devalued the entire notion of offshore processing. The only consolation for the government was that the court had reduced the options available to all political parties. Secondly, the Wikileaks saga revealed that Rudd may no longer be — and perhaps never was — Labor’s trump card in the realm of foreign policy. American assessments of the foreign minister’s character and judgment were in parts scathing. The Obama administration, nonetheless, appeared to readily and usefully absorb his analysis of Chinese politics. Quite how revelations of Rudd’s conversations with Clinton will affect his relations with the leaders of the Chinese Communist Party is another matter. It may well be that Rudd’s influence on Chinese leaders was always wildly overestimated, but in any case it seemed likely that the foreign minister would spend some time rebuilding ties with Beijing in 2011. A third development — which hitherto had applied more in the realm of perception than reality — similarly threatened to limit the options open to future Australian governments of all stripes: the intensifying debate over alliance management that Hugh White’s essay instigated. Judgments about what sort of region — and what sort of China — Australia will face were imprinted in issues such as ...